Aesthetics of the Flesh: curricular insurrection of the ugly body - Roseiro, Steferson Zanoni; Rodrigues, Alexsandro; Alvim (Universidade Federal do Espírito Santo – UFES, Vitória/ES, Brazil), Davis Moreira (Revista Brasileira de Estudos da Presença, 2022)
The essay aims to think the existence of an ugly body as a curricular insurrection against the embellishing capitalistic strategies and take bets on the possibility of questioning the beauty. Despite of an organizational curriculum policy that praises the aseptic, pretty and seducing body, this writing proposes to think the body beyond the aesthetics capitalistic enslavement. If it is an aesthetic imperative, the body mocks on ugliness.